The U.S. Military and the Influenza Pandemic of 1918–1919 - Byerly, Carol R. (Association of Schools of Public Health, 2010)
The American military experience in World War I and the influenza pandemic were closely intertwined. The war fostered influenza in the crowded conditions of military camps in the United States and in the trenches of the Western Front in Europe. The virus traveled with military personnel from camp to camp and across the Atlantic, and at the height of the American military involvement in the war, September through November 1918, influenza and pneumonia sickened 20% to 40% of U.S. Army and Navy personnel. These high morbidity rates interfered with induction and training schedules in the United States and rendered hundreds of thousands of military personnel non-effective. During the American Expeditionary Forces' campaign at Meuse-Argonne, the epidemic diverted urgently needed resources from combat support to transporting and caring for the sick and the dead. Influenza and pneumonia killed more American soldiers and sailors during the war than did enemy weapons.